Supporting climate change adaptation using historical climate analysis. (27th May 2020) - Dorward, Peter; Osbahr, Henny; Sutcliffe, Chloe; Mbeche, Robert
ABSTRACT: Climate change and variability presents a challenge for rural communities in developing countries. Bridging organizations help align stakeholder and local perspectives and mediate communication that shapes adaptation responses. We argue that a first step for adaptation projects is to determine the nature of the climate norms and how climate is changing. This paper explores the degree to which development organizations in Kenya, Uganda and Tanzania used analysis of local historical climate information in project aims, planning and design. This included 67 participants, managing 102 community-level climate-related agricultural projects, and three NGO case studies. Most focused on low-regret options. The majority of projects enhanced awareness of climate change and variability, but only 7% had used historical climate information during planning. Instead, projects relied on general knowledge or farmers' perceptions, which sometimes differ from analyzed historical climate information, potentially leading reinforcement of perceptions. It is vital that bridging organizations and policy makers value analyzed historical climate information when determining climate norms (including variability) and identify what data shows regarding how climate is changing. This is essential for planning with stakeholders the suitability of alternative crops and cultivars and ensuring other relevant environmental factors influencing agricultural production are considered.